Evaluasi Data Curah Hujan Satelit TRMM Dan GPM Terhadap Data Curah Hujan Observasi Di Kalimantan Tengah: Evaluation Rainfall Data Of TRMM And GPM Sattelites Based On Observation Rainfall Data Over Central Kalimantan - Dewi Kartika; Nomeritae Nomeritae; I Made Kamiana (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Rainfall is an indispensable component of hydrological analysis. However, the observational rainfall data has problems such as incomplete and shorter data. Rainfall measurements using high resolution and wide area coverage satellites provide a potential alternative for various hydrological analyses. But the measurement of rainfall using satellites is not necessarily accurate due to the difference in resolution of the observational rainfall data, especially in Central Kalimantan Province. This study aims to determine the accuracy of satellite rainfall data based on observational rain data and evaluate it. Evaluation is done by looking for the relationship between the two-rainfall data using a regression model. The results showed that the TRMM total grid rainfall data (R2 = 0.5233) had a higher correlation to the observational rainfall data compared to the GPM rainfall data (R2 = 0.3909). Furthermore, a discharge analysis was carried out in one of the watersheds in Central Kalimantan, namely the Kahayan watershed using the Nakayasu Hydrograph Synthesis Unit method with a certain return period with satellite rainfall data input which has a fairly good accuracy based on the results of the analysis. The estimated discharge with return periods of 2, 5, 10, 25, and 50 years for TRMM rainfall data before correction are 1976.74m3/s, 2165.66 m3/s, 2239.19 m3/s, 2313.63 m3/s, 2375.69 m3/s respectively, and for the estimated discharge after correction are 2549.35 m3/s, 2670.59 m3/s, 2736.42 m3/s, 2801.37 m3/s, 2854.82 m3/s.